(3GdbhdfLs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdMeO ddg hHYO abO NGWHfi HGdCeQ GdLdjd HYKQI GdOhdI Yf Gdedc caGjI Gddg ai LejY JUQaGJg s
(3BNQgG (B:s
(3GdUfa hjbhi GdCeYGA hbO SHb PcQ LejY Pdc hbO GSJhajfG Gdbhd Yf GdZQV s
(3fSNI CNQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
GAL - (3GdLRA (B1 - (3U (B812 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B150 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI QVGQGeHhQ (B(423(5)) s
Keywords: (3GdWHs